Case Report: Loeffler endocarditis as a cause of left ventricular thrombosis in young women: a case study and literature review - Cui, Yue; Shi, Yugen; Wang, Xiaojun (Frontiers in Cardiovascular Medicine, 2024)
It is unusual for young patients without any underlying diseases to experience sudden cerebral infarction and heart failure. Here, we report a rare case of a 28-year-old female patient who presented with chest tightness and dizziness. Left ventricular thrombus formation and cardiac insufficiency were evident on echocardiogram, while multiple acute or subacute cerebral infarctions were visible on brain magnetic resonance imaging. We preliminarily determined that this was a different manifestation of the same disease. After investigating the cause, we diagnosed the patient with Loeffler endocarditis caused by idiopathic eosinophilia syndrome involving the heart. Although no endocardial biopsy was performed, this diagnosis was confirmed through cardiac magnetic resonance imaging (CMR). After drug treatment consisting of corticosteroids and anticoagulants, the eosinophil count decreased significantly; however, the thrombus did not completely disappear, as assessed in multiple follow-up echocardiogram sessions. Further exploration of the tissue composition of the patient's left ventricular mass suggested that the mass was a mixture of thrombus and eosinophilic granulation tissue. The addition of imatinib to the treatment plan had a good therapeutic effect, and the patient's left ventricular mass completely disappeared. Loeffler endocarditis progresses rapidly and requires early identification and intervention by clinicians. This case emphasizes that, despite the lack of an endocardial biopsy, the early diagnosis of Loeffler endocarditis can be made through CMR, while avoiding the occurrence of irreversible endocardial fibrosis. We also explored the nature of the patient's cardiac mass and proposed different insights. The nature of cardiac mass varies in different stages of Loeffler endocarditis, and individualized treatment strategies are needed.